A Study on Heuristic Algorithms Combined With LR on a DNN-Based IDS Model to Detect IoT Attacks - Thanh Thuy, Tran Thi; Duc Thuan, Luong; Hong Duc, Nguyen; Trong Minh, Hoang (Institute of Automation and Computer Science, Brno University of Technology, 2023)
Current security challenges are made more difficult by the complexity and difficulty of spotting cyberattacks due to the Internet of Things explosive growth in connected devices and apps. Therefore, various sophisticated attack detection techniques have been created to address these issues in recent years. Due to their effectiveness and scalability, machine learning-based intrusion detection systems (IDSs) have increased. However, several factors, such as the characteristics of the training dataset and the training model, affect how well these AI-based systems identify attacks. In particular, the heuristic algorithms (GA, PSO, CSO, FA) optimized by the logistic regression (LR) approach employ it to pick critical features of a dataset and deal with data imbalance problems. This study offers an intrusion detection system (IDS) based on a deep neural network and heuristic algorithms combined with LR to boost the accuracy of attack detections. Our proposed model has a high attack detection rate of up to 99% when testing on the IoT-23 dataset.
Keywords: Intrusion Detection System; Deep Neuron Network; Heuristic Algorithms; IoT-23 dataset